2023
DOI: 10.1038/s41467-023-37380-5
|View full text |Cite
|
Sign up to set email alerts
|

Observation of phonon Poiseuille flow in isotopically purified graphite ribbons

Abstract: In recent times, the unique collective transport physics of phonon hydrodynamics motivates theoreticians and experimentalists to explore it in micro- and nanoscale and at elevated temperatures. Graphitic materials have been predicted to facilitate hydrodynamic heat transport with their intrinsically strong normal scattering. However, owing to the experimental difficulties and vague theoretical understanding, the observation of phonon Poiseuille flow in graphitic systems remains challenging. In this study, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…However, the experimental evidence on the hydrodynamic transport of phonon and electron fluids remains scarce [14][15][16][17][18] until recently. With the emergence of low-dimensional materials and extremely pure crystals, experiments have revealed an increasing number of exotic electrical and thermal properties of these materials including vortex in an electron fluid [19], Poiseuille electron and phonon flows [20][21][22][23][24][25], negative nonlocal resistance [26][27][28][29][30], violation of the Wiedemann-Franz law [31,32], the extremely high thermal conductivity of suspended graphene [33][34][35][36], second sound in graphite and Ge [37][38][39], and hydrodynamic heat transport in semiconductors [40][41][42][43]. Recently, Xiang et al found that the G-K equations are more suitable for data analysis of time-domain thermoreflectance technique for measuring thermal conductivity of Si and Ge than the diffusive heat conduction model [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental evidence on the hydrodynamic transport of phonon and electron fluids remains scarce [14][15][16][17][18] until recently. With the emergence of low-dimensional materials and extremely pure crystals, experiments have revealed an increasing number of exotic electrical and thermal properties of these materials including vortex in an electron fluid [19], Poiseuille electron and phonon flows [20][21][22][23][24][25], negative nonlocal resistance [26][27][28][29][30], violation of the Wiedemann-Franz law [31,32], the extremely high thermal conductivity of suspended graphene [33][34][35][36], second sound in graphite and Ge [37][38][39], and hydrodynamic heat transport in semiconductors [40][41][42][43]. Recently, Xiang et al found that the G-K equations are more suitable for data analysis of time-domain thermoreflectance technique for measuring thermal conductivity of Si and Ge than the diffusive heat conduction model [44].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Poiseuille flow and second sound have been observed in diverse, submillimeter-sized samples including graphene nanostructures at low temperatures. 28,32–36…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al observed unusual transient lattice cooling near the adiabatic center of a 15 µmdiameter ring-shape pump beam on graphite at temperatures between 80 and 120 K [13]. Huang et al have demonstrated experimentally the phonon Poiseuille flow in isotopicallypurified graphite ribbons [14]. These phonon hydrodynamic experiments at elevated temperatures have motivated many theoretical works to declare the evidence of the hydrodynamic regime as well as to study various types of viscous phonon flows.…”
Section: Introductionmentioning
confidence: 99%